Introducing Our New Chief Editor - Josep M. Trigo-Rodríguez (Advances in Astronomy)
Advances in Astronomy is pleased to announce the appointment of Prof Josep Trigo Rodríguez as its new Chief Editor. In this Editorial, Prof Trigo introduces himself, describes some of the journal’s journey and current status, and shares his vision and aspirations for its future.